Optimization of Climatic Conditions Affecting Determination of the Amount of Water Needed by Plants in Relation to Their Life Cycle with Particle Swarm Optimization, and Determining the Optimum Irrigation Schedule. (21st July 2021) - Bülbül, Mehmet Akif; Öztürk, Celal; Işık, Mehmet Fatih
Abstract: Plants' need for water has become a topic of research for the agriculture industry. The fact that plant species are very diverse and each plant's need for water varies makes it difficult to plan programs with conventional irrigation methods. Plants exhibit different stages from their seed time to harvest season. Each stage is defined within as days, and the amount of water needed by the plant throughout these stages varies. In this study, optimization of the irrigation schedule for each stage of a plant is provided. The amount of water needed by the plant was first figured out by using climatic data, and then, these values were recalculated in relation to the plant type. The amount of water needed at each stage was related to the plant type by using particle swarm optimization. The obtained results revealed the optimal irrigation schedule for each stage with the obtained data.